1991
DOI: 10.1016/0014-5793(91)80812-h
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mammalian, chicken and Xenopus brain‐derived neurotrophic factor coding sequences

Abstract: We have used the polyrnerase chain reaction (PCR) to amplify and clone coding sequences of the mature region of brain-derived neurotrophic factor (BDNF) from monkey, rat, chicken and XenopuF genomic DNA. Consistent with previous reports, the predicted amino acid sequences obtained in this manner from monkey and rat were identi c?J !o other mammalian BDNF sequences. 'The chicken and Xenopus BDNF sequences arc also highly conserved, but contain 7 and 8 amix acid substitutions, respectively, compared to mammalian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…IA). The predicted amino acid sequence of the mature chicken NT-3 protein was then compared to that of chicken NGF (Ebendal er al., 1986) and chicken BDNF (Isackson et al, 1991) and shown to be 60.1 and 58.1 % identical to chicken NGF and BDNF, respectively ( Fig. 1B).…”
Section: Isolation Of Chicken Bdnf and Nt-3 Genesmentioning
confidence: 83%
“…IA). The predicted amino acid sequence of the mature chicken NT-3 protein was then compared to that of chicken NGF (Ebendal er al., 1986) and chicken BDNF (Isackson et al, 1991) and shown to be 60.1 and 58.1 % identical to chicken NGF and BDNF, respectively ( Fig. 1B).…”
Section: Isolation Of Chicken Bdnf and Nt-3 Genesmentioning
confidence: 83%
“…Under physiological conditions, the processing from pro-BDNF to mBDNF is important for neuronal development, neuronal survival, and synaptic plasticity. The mBDNF and its receptor, TrkB, are widely expressed in the developing and adult mammalian brains [ 173 , 174 ]. The pathways associated with changes in neuronal excitability are triggered by the binding of mBDNF to TrkB, indicating that TrkB activation is crucial for controlling the survival, morphogenesis, and plasticity of neurons [ 175 ].…”
Section: Potential Mechanisms Underlying Bdnf’s Effect On Admentioning
confidence: 99%
“…BDNF has been cloned from pig, mouse, rat, and human (Leibrock et al, 1989;Hofer et al, 1990;Maisonpierre et al, 1991). Partial sequence is known also from chicken and Xenopus (Hallbook et al, 1991;Isackson et al, 1991).…”
Section: The Members Of the Ngf Gene Familymentioning
confidence: 99%